Inhibitory projections connecting the dentate gyri in the two hemispheres support spatial and contextual memory - Yen, Ting-Yun; Huang, Xu; MacLaren, Duncan Archibald Allan; Schlesiger, Magdalene; Monyer, Hannah; Lien, Cheng-Chang (Cell reports, 2022)
The dentate gyrus (DG) receives substantial input from the homologous brain area of the contralateral hemisphere. This input is by and large excitatory. Viral-tracing experiments provided anatomical evidence for the existence of GABAergic connectivity between the two DGs, but the function of these projections has remained elusive. Combining electrophysiological and optogenetic approaches, we demonstrate that somatostatin-expressing contralateral DG (SOM+ cDG)-projecting neurons preferentially engage dendrite-targeting interneurons over principal neurons. Single-unit recordings from freely moving mice reveal that optogenetic stimulation of SOM+ cDG projections modulates the activity of GABAergic neurons and principal neurons over multiple timescales. Importantly, we demonstrate that optogenetic silencing of SOM+ cDG projections during spatial memory encoding, but not during memory retrieval, results in compromised DG-dependent memory. Moreover, optogenetic stimulation of SOM+ cDG projections is sufficient to disrupt contextual memory recall. Collectively, our findings reveal that SOM+ long-range projections mediate inter-DG inhibition and contribute to learning and memory.